DTV-T2 coverage : comparison of measured and predicated signals (Part B) - Akshaya Mahesh Kumar (2015)
Currently, transmissions for television signals in Singapore is via DVB8T and DVB8T2. More and more areas in Singapore are starting to transmit DVB8T2 as it is the latest extension of DVB8T. With DVB8T2, more channels can be transmitted. Moreoever, it is more robust and effective than DVB8T. In this project, the signal propagations for both DVB8T and DVB8T2 are studied and compared. Comparisons are also drawn under the usage of omnidirectional and directional antennas, so that it can be observed how DVB8T and DVB8T2 are affected under different circumstances. Different premises were also chosen for measurements so that a wider range of data could be collated. With the results of this project, further studies could be done on DVB8T2 propagation. Ways of improving digital television quality in Singapore could also be further studied to ensure citizens reap maximum benefits. The experiments conducted in this project were predominantly in the NTU campus, and HDB flats in Bukit Batok and Bukit Panjang. Points of measurements were conducted along corridors of the premises or inside the HDB flats. The results and analysis of these experiments could help to identify major factors that affect signal power strength at various points, which are height of point of measurement and presence of line-of-sight. The results show that in the presence of a higher height from ground and line-of-sight from transmitter, signal strength is higher.